2015
DOI: 10.1542/peds.2014-3503
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Benefits and Challenges of Long-term Eculizumab in Atypical Hemolytic Uremic Syndrome

Abstract: Atypical hemolytic uremic syndrome (aHUS) is caused by dysregulation of the complement system, leading to complement overactivation. A humanized anti-C5 monoclonal antibody, eculizumab, has been available for the treatment of aHUS since 2011. The long-term safety and efficacy of this novel drug in the pediatric population remain under review. We present a child with a hybrid CFH/CFHR3 gene who, having had multiple disease relapses despite optimal treatment with plasma exchange, commenced eculizumab therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Meningococcal disease following MenACWY vaccination in eculizumab recipients has been reported previously ( 1 , 5 ), and in vitro data have shown that eculizumab impairs meningococcal killing in whole blood even in subjects vaccinated against the relevant meningococcal serogroup ( 6 ). In addition, although nongroupable N. meningitidis is often carried asymptomatically in the nasopharynx, it rarely causes disease in healthy persons ( 7 ).…”
Section: Discussionmentioning
confidence: 72%
“…Meningococcal disease following MenACWY vaccination in eculizumab recipients has been reported previously ( 1 , 5 ), and in vitro data have shown that eculizumab impairs meningococcal killing in whole blood even in subjects vaccinated against the relevant meningococcal serogroup ( 6 ). In addition, although nongroupable N. meningitidis is often carried asymptomatically in the nasopharynx, it rarely causes disease in healthy persons ( 7 ).…”
Section: Discussionmentioning
confidence: 72%
“…For this reason, meningococcal vaccination is considered mandatory; however, serologic response is variable (39), and the efficacy of vaccination in the context of complement blockade is uncertain (6). Long-term antibiotic prophylaxis is therefore recommended for the duration of treatment and up to 3 months after withdrawal (6), although meningococcal infection can occur despite these precautions (40,41). Thus, patient education regarding vigilance is essential.…”
Section: Complement-inhibiting Therapymentioning
confidence: 99%
“…The long‐term safety of eculizumab is promising yet remains uncertain. Safety has been previously reported in children with aHUS treated for up to 4 years . In patients with paroxysmal nocturnal haemoglobinuria, long‐term safety data are available in excess of 8 years .…”
Section: Discussionmentioning
confidence: 99%